Optimalisasi Leadership dan Sarana Belajar Sebagai Pilar Pendidikan Sekolah Alam Melalui Inisiasi Outbound di Sekolah Alam Rumbai Pekanbaru - Berry Kurnia Vilmala; Afdhil Hafid; Defrizal Hamka (Jurnal Pengabdian UntukMu NegeRI, 2020)
One of the shortcomings in the implementation of education in schools is the lack of a forum that can facilitate student leadership which is integrated with learning in the Classroom. In general, Leadership is carried out in extracurricular activities in schools. The implementation of Leadership training has limited time in its implementation and is felt to be less than optimal. Leadership is separate from student learning activities. UMRI has experts in the field of Science (IPA) and Education under the auspices of the Faculty of Teacher Training and Education and the field of Technology Design under the auspices of the Faculty of Computer Science who can contribute their knowledge to the Leadership optimization program and the means of learning together with nature through outbound initiation at the Rumbai Nature School. The main activity that would be carried out in this program is to design and create an integrated outbound facility with the Natural Joint Learning facilities in the Sekolah Alam Rumbai environment. The output that is expected to be generated from this activity is the availability of integrated outbound facilities to support Leadership through outbound and scientific logic through Student Learning Together Nature can be optimized.